The Collapse of Mud Living Economies in Bessie Head2019;s Serowe the Village of the Rain Wind (Global Journal of Science Frontier Research, 2018)
Bessie Head s ethnographic reportage in Serowe The Village of the Rain Wind is an important historical document to locate the collapse of sustainable communities and reproductive generation In this essay I argue that Head s ethnographic reportage at this historical intersection at the cusp of neoliberalism chronicles how international national and regional politics in collusion with transnational pharmaceutical companies undermine women s reproductive bodies and family structures The result is the reproductive collapse of tribal communities and the absorption of indigenous peoples into the global capitalist economy
Keywords: bessie head; botswana; capitalism; reproductive collapse; reproductive control; reproductive justice; indigenous communities; ethnography